2023
DOI: 10.1002/asia.202300006
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solar Cells: Physical Principle and Recent Advances

Abstract: Organic solar cells (OSC) based on organic semiconductor materials that convert solar energy into electric energy have been constantly developing at present, and also an effective way to solve the energy crisis and reduce carbon emissions. In the past several decades, efforts have been made to improve the power conversion efficiency (PCE) of OSCs. During this period, a variety of structural and material forms of OSCs have evolved. Commercializing OSCs, extending their service life and exploring their future de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Donor PM6 and acceptor Y6 manifested great advantages as active layers of the bulk heterojunction OSCs, 19,[47][48][49][50][51][52][53] while the physical mechanism of FRET and ICT for Efficient Y6:PM6 as active layers should be interpreted in detail. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Donor PM6 and acceptor Y6 manifested great advantages as active layers of the bulk heterojunction OSCs, 19,[47][48][49][50][51][52][53] while the physical mechanism of FRET and ICT for Efficient Y6:PM6 as active layers should be interpreted in detail. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10 Organic solar cells (OSCs) have the advantages of light harvesting, comprehensive material sources, flexible and translucent devices, etc., and they have become a new energy technology with prospects for various applications. [11][12][13] OSCs are usually prepared from a mixture of donor and acceptor materials. In early studies, non-fullerene receptor materials were ignored because of their low efficiency, but until 2015, Zhang et al 14 reported a high-cratered non-fullerene acceptor with benzothiophene as the core and dicyan indention as the end group.…”
Section: Introductionmentioning
confidence: 99%
“…1) is a stable free radical that can be applied as a dopant in active layers of thin-film organic solar cells (OSCs) to improve their characteristics. [1][2][3] It has been reported 4,5 that Gx at a concentration of 2 wt% or 3 wt% significantly increases the polymer-fullerene OSC efficiency by increasing photocurrent generation. To explain this enhancement, it was suggested that the radical nature of Gx could allow the formation of photoinduced charge carriers of electron-hole pairs in the triplet state, so that their recombination decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of cost-effectiveness, portability, and semitransparency, solution-processed polymer solar cells (PSCs) have drawn significant interest as a future power source over the last few decades. [1][2][3][4][5][6][7][8][9][10] Among the systems implementing various PSCs, all-polymer solar cells (all-PSCs), based on a combination of conjugated polymer donors and acceptors as the active layer, have shown a more excellent morphological stability under illumination, thermal stress, and mechanical stress than solar cells with small molecules. [11][12][13][14][15][16][17][18][19][20][21][22] Since the initial research on all-PSCs was published in 2010, two kinds of polymers are mainly employed for n-type, in contrast to p-type, which has many candidates.…”
Section: Introductionmentioning
confidence: 99%